Curative Bioactivity of Moringa (Moringa Oleifera Lam.) Seed Oil against Callosobruchus Maculatus F. Infested Cowpea (Vigna Unguiculata L. Walp.) Grain in Storage - Z, Dauda; Degri, M. M; Gadzama, U. N; Hassan, M (International Journal of Sustainable Agricultural Research, 2014)
Farmers, households as well as grain merchants have to contend with infested stored cowpea grain once attacked by Callosobruchus maculatus (F.). They could be compelled to consume, sale at low economic value or find other way of salvaging the grains from total damage and loss. This paper reports the curative effect of moringa (Moringa oleifera Lam.) seed oil (MSO) in mitigating C. maculatus damage and loss to freshly infested cowpea grains in storage. Ten grams cowpea grains of three varieties (Gwalam, Borno brown, and Banjara) were each weighed into a 200 ml bottle in three replicates for un-treated and four levels of MSO treatments (0.1, 0.2, 0.4 and 0.6 ml). Three pairs of opposite sex adult C. maculatus 0-48 hrs old were used to infest grains in each replicate. Insects were removed five days after infestation and the number of eggs laid on grains in each replicate counted. MSO treatments were carried out at five and eight days after infestation. The number of adults that emerged was counted daily throughout the first filial generation (F1). All data were subjected to analysis of variance at 5% level of probability. Significantly different means were determined using Least Significant Difference. Results indicated statistical significances (P<0.05) between treated and un-treated infested grains of each variety. This implied that MSO is effective in mitigating C. maculatus damage to cowpea grain in storage. Grains infested with 1-8 days old cowpea bruchid eggs could be salvage from total damage and loss. Control was achieved mainly through ovicidal action and / or adverse effect of the oil on early larval instars thereby reducing and / or eliminating the damaging effect of C. maculatus.